2001
DOI: 10.7589/0090-3558-37.4.775
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Ivermectin Treatment of Sarcoptic Mange and Establishment of a Mange-Free Population of Spanish Ibex

Abstract: Ivermectin was used to treat sarcoptic mange in Spanish ibex (Capra pyrenaica hispanica). Its therapeutic effectiveness was analyzed when it was administered through subcutaneous injection, to sick animals in the consolidation stage of mange (third phase) and, with double injections to chronically affected animals (fourth phase) at a dosage of 0.2 or 0.4 mg/kg body weight (bw). Three wk after treatment, the animals in the third phase of mange treated with a high dose (0.4 mg/kg bw) of ivermectin were completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 15 publications
1
32
1
1
Order By: Relevance
“…Selective administration of ivermectin has been reported to be successful in treating mange infestation in goats (Leon-Vizcaino et al, 2001;Marimuthu et al, 2015). However, the treatment of Chorioptic mange with ivermectin has proved to be less effective in this study as lesions persisted even after the completion of the recommended treatment regime.…”
Section: Research Journal For Veterinary Practitioners April 2015 | Vcontrasting
confidence: 41%
See 1 more Smart Citation
“…Selective administration of ivermectin has been reported to be successful in treating mange infestation in goats (Leon-Vizcaino et al, 2001;Marimuthu et al, 2015). However, the treatment of Chorioptic mange with ivermectin has proved to be less effective in this study as lesions persisted even after the completion of the recommended treatment regime.…”
Section: Research Journal For Veterinary Practitioners April 2015 | Vcontrasting
confidence: 41%
“…Scabies scrapings can be collected deep around scabs until blood oozes out, samples are then processed and viewed under the microscope to identify the mite (Chanie et al, 2010). Treatment of mange is mostly done using ivermectin at the dose of 0.2 mg/kg, doramectin at 200 µg/kg at weekly intervals (Leon-Vizcaino et al, 2001;Marimuthu et al, 2015). Many literature have reported that chemical dipping (0.05% diaznon, 0.1% phoxin, lime sulphur and triclorfon) is the most effective way Case Report Abstract | A Jamnapari buck was presented during a farm visit with a history of skin itching and loss of hair.…”
mentioning
confidence: 99%
“…However, goats treated with ivermectin showed significant improvements in the reduction of adult mite and egg count, and in the appearance of skin coat post treatment, as there was marked reduction in the epidermal tunnel height and diameter after 4 weeks of treatment , as ivermectin has cleared all mite stages from the skin and gross lesions started resolving at day 11 of second treatment, this agrees with the work of Leon-Vizcaıno et al (2001) in wild goat and Alayande et al (2002) in West African dwarf goats who noted that there was marked decrease in the mean number of adult mites at 7 days post treatment with ivermectin in goats and at day 14 post treatment, almost all goats were cleared of infestation. This implies that ivermectin being systemic is fast in its mode of action and effectively rid the skin of the goats of infestation of mites and also neutralizing the histamine released by destroyed cells due to these burrowing mites thereby relieving the treated goats.…”
Section: Discussion and Conclussionsupporting
confidence: 87%
“…IVM is relatively nontoxic to most vertebrates, and so it has been used to lower filaremia in humans, thereby significantly reducing the transmission of filariasis (Boatin et al 1998, Foley et al 2000. In veterinary medicine, wildlife management, and even in aquaculture, IVM has valuable efficacy against a wide range of parasitic nematodes and arthropods (Campbell et al 1983, Jackson 1989, Strong 1993, Davies and Rodger 2001, Leó n-Vizcaíno et al 2001, Geary 2005.…”
Section: Introductionmentioning
confidence: 99%